Unravelling Thermal Comfort: Investigating Tropical Conditions at Bandar Bukit Raja Mosque, Klang - Aznan, Khaulah; Saji, Nordalila (Progress in Engineering Application and Technology, 2024)
This study investigates thermal comfort conditions at the Bandar Bukit Raja Mosque in Klang, Malaysia, focusing on the impact of air temperature, humidity, and air movement on occupant comfort in a tropical climate. Using the LSI LASTEM HeatShield instrument, physical measurements were conducted, and perception surveys of 86 respondents were analyzed. The reliability of the survey instrument was confirmed with a Cronbach’s Alpha value of 0.819, indicating good internal consistency. The survey utilized the Fanger Model to calculate Predicted Mean Vote (PMV) and Predicted Percentage of Dissatisfied (PPD). Additionally, the Adaptive Index Equation was used to determine Operative Temperature (T_o), and Temperature Neutral Operative (Tneutop). The study found that environmental measurements and survey results consistently exceeded the thermal comfort limits recommended by ASHRAE Standard 55, indicating significant discomfort among occupants. Specifically, PMV values ranged from 1.4 to 2.6, and PPD values ranged from 48% to 94.7%, demonstrating a substantial level of thermal dissatisfaction. The highest dissatisfaction was observed during midday and afternoon sessions, with air temperatures peaking at 32.4°C and relative humidity levels reaching up to 84.6%. The study underscores the need for improved thermal management strategies, including enhanced ventilation, humidity control, and architectural modifications to mitigate heat gain. These findings contribute to a broader understanding of thermal comfort in naturally ventilated spaces and emphasize the importance of sustainable building practices in tropical climates to enhance indoor environmental quality and occupant well-being.